Modulating the gut microbiota in Crohn’s disease: a pilot study on the impact of a plant-based diet with DNA-based monitoring - Østergaard, Stine Karstenskov; Cetin, Zeynep; Rasmussen, Henrik Højgaard; Lærke, Helle Nygaard; Holst, Mette; Lauridsen, Charlotte; Nielsen, Jeppe Lund (Frontiers in Nutrition, 2024)
This study investigates the effects of a plant-based diet (PBD) on gut microbiota composition and inflammation in Crohn's Disease (CD) patients, using a combination of dietary assessments and advanced molecular techniques. Fourteen patients completed a 12-week intervention, with dietary adherence monitored through both self-reported food diaries and sequencing of the trnL gene to detect plant residues in fecal samples. TrnL sequencing identified 55 plant genera, compared to the 41 reported in food diaries, demonstrating a more accurate measurement of plant residue diversity in fecal samples, overcoming limitations of self-reported dietary data. The PBD led to a significant 1.4-fold increase in plant intake by week 4, which correlated with a marked increase in bacterial diversity, which is significant given the role of reduced microbial diversity in inflammatory bowel disease (IBD) pathogenesis. Microbial analysis revealed increased abundance of key genera, such as Faecalibacterium and Bacteroides, both known to be underrepresented in CD patients. Additionally, fecal calprotectin levels, a marker of intestinal inflammation, decreased from 472 mg/kg at baseline to 207 mg/kg at week 12. These findings suggest that a PBD can positively influence gut microbiota and decrease enteric inflammation in CD patients, while also establishing that trnL sequencing can be a useful tool for dietary adherence assessment in clinical studies.